E|Benchmark - A pioneering method for process planning and sustainable manufacturing strategies - Kreitlein, Sven; Spreng, Simon; Franke, Jörg (Procedia CIRP, 2015)
This paper introduces a method for the assessment and evaluation of energy efficiency of the manufacturing processes in the production. A directive for energy efficiency benchmarking has already been published, however, due to its lack of defined energy indicators, it does not allow for a significant comparison. In a preliminary step, 120 currently used energy indicators were examined to assess their suitability as an energy benchmark. Based thereon, three approaches for the assessment of energy efficiency of the manufacturing processes in the production as well as a method for transferring the system by means of relevant indicators at the sectorial and corporate levels were developed. In the following, the approach of "minimal value calculation," which was identified as being the most advantageous, is presented in detail. The basic idea is the comparison and evaluation of energy efficiency based on the ratio of the theoretically required energy consumption to the actual energy consumption. Depending on the analysis of influencing factors, a model highlighting their dependencies could be established. The developed system hinges on a successive calculation of the minimum value. Each of these minimum types can be put in relation to the measured energy consumption, however, depending on the chosen basis, the conclusion and focus of the calculated key figure may vary. By using the material minimum as a basis, the actually existing energy savings become visible. The method will be put to test through an exemplary application for processes in the fields of electronics production, electrical engineering, and production machining. This course of action allows the validation of the developed approach and reveals the potential of this method.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Energy efficiency validation; Manufacturing strategies; Production systems